Struktur komunitas mangrove di Pulau Mare, Kota Tidore Kepulauan, Provinsi Maluku Utara (Community structure of mangrove in Mare Island, Tidore City, Maluka Utara Province - Nebuchadnezzar Akbar; Abdurrachman Baksir; Irmalita Tahir; Dondy Arafat (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2016)
This study aimed to obtain information mangrove ecological index in Mare Island, Tidore Kepulauan, North Maluku. Collecting data in 2015, divided into three locations were determined based representation and the representation of mangrove. The sampling of mangrove using